Study on the interaction between a screw dislocation and circular holes or rigid inclusions by using the angular basis function in conjunction with bipolar coordinates. (February 2023) - Chen, Jeng-Tzong; Kao, Shing-Kai; Tai, Wei-Chen; Lee, Ying-Te; Lee, Jia-Wei; Chou, Yen-Ting
In this paper, the degenerate kernel in conjunction with the bipolar coordinates is employed to solve the anti-plane problems of interaction between a screw dislocation and circular holes or rigid inclusions. Once the degenerate kernel of the angular basis function (ABF) is provided in terms of the bipolar coordinates, the analytical solution for cases of one or two circular holes and rigid inclusions can be derived. Not only the radial basis function (RBF) but also the ABF is used. First, the observer objectivity of the degenerate kernel in terms of the bipolar coordinates is examined numerically. A special case, one circular hole or rigid inclusion, is considered to demonstrate the validity of the present approach. Finally, the cases containing two circular holes and two circular rigid inclusions were examined. The comparison between available results and ours is well done. Besides, for the solutions of two holes and rigid inclusions, it is interesting to find that the present method provides an analytical solution with a series form of explicitly determined coefficients, while the coefficients provided by the complex variable need to be determined using the recursive formulae.